2022
DOI: 10.1155/2022/4370341
|View full text |Cite|
|
Sign up to set email alerts
|

Multiparameter Magnetic Resonance Quantitative Evaluation of Pancreatic Cancer with Vascular Invasion

Abstract: Objective. To analyze the value of multiparameter magnetic resonance (mpMRI) in the diagnosis of pancreatic cancer with vascular invasion from two aspects: morphology and function, so as to provide a reliable diagnostic basis for preparing the clinical treatment plans. Methods. Totally 31 case data of pancreatic cancer patients diagnosed in our hospital from January 2020 to March 2021 were enrolled in this study. All patients underwent multiparameter magnetic resonance imaging (T1WI, T2WI, DKI, and DCE-MRI) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…29 MD parameter reflects the diffusion state of water molecules within the tumor and is similar to the ADC value in the DWI model. 35 This study found that MD values were moderately positively correlated with RSG in PCa. MD values were higher in high RSG than in low RSG, and the AUC was better for MD than for ADC values, which is consistent with a previous study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…29 MD parameter reflects the diffusion state of water molecules within the tumor and is similar to the ADC value in the DWI model. 35 This study found that MD values were moderately positively correlated with RSG in PCa. MD values were higher in high RSG than in low RSG, and the AUC was better for MD than for ADC values, which is consistent with a previous study.…”
Section: Discussionmentioning
confidence: 52%
“…DKI can reflect the tissue's non‐Gaussian movement pattern of water molecules 29 . MD parameter reflects the diffusion state of water molecules within the tumor and is similar to the ADC value in the DWI model 35 . This study found that MD values were moderately positively correlated with RSG in PCa.…”
Section: Discussionmentioning
confidence: 54%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%